History after Hitler : a transatlantic enterprise - Stelzel, Philipp (Intellectual history of the modern age., 2019)
The decades following the end of World War II witnessed the establishment of a large and diverse German-American scholarly community studying modern German history. As West Germany's formerly deeply nationalist academic establishment began to reconcile itself with postwar liberalism, American historians played a crucial role, both assisting and learning from their German counterparts' efforts to make sense of the Nazi past-and to reconstruct how German society viewed it.In History After Hitler, Philipp Stelzel puts this story center stage for the first time, positioning the dialogue between German and American historians as a key part of the intellectual history of the Federal Republic and of Cold War transatlantic relations. Making extensive use of previously inaccessible or unexplored personal papers and institutional files in German and American archives, Stelzel demonstrates that several factors fostered the growth of this transatlantic scholarly community. As a result of both National Socialism and the Cold War, American interest in Germany grew remarkably. In addition, a small but increasingly influential cohort of German émigré historians working in the United States served as transatlantic intermediaries. Finally, the strong appeal of American academia to West German historians of different generations led many of them to form and maintain close ties with their American colleagues.History After Hitler explores how these historians participated as public intellectuals in debates about how to cope with the Nazi past, believing that the historical awareness of West German citizens would bolster the Federal Republic's democratization. Stelzel also corrects simplistic arguments regarding the supposed "Westernization" of the Federal Republic, emphasizing that American scholars, too, benefited from the transatlantic conversation. History After Hitler makes the case that, together, German and American historians contributed to the development of postwar German culture, intellectual life, and national self-understanding.